WACANA ISLAM ISLAM LIBERAL: ANALISIS ARTIKEL DI MEDIA ONLINE JARINGAN ISLAM LIBERAL (www.islamlib.com) - Agus Riyanto (SPEKTRUM, 2008)
AbstractIslamic Liberal Discources is one of Islamic movement which has shared on Reformation era besides the other Islamic types like Radical Islam. Both of them are usually in discources conflict because the difference religion concern. The article will describe how Islamic Liberal Network, construct discource on on line media, www.Islamlib.comKey words : Islamic Liberal discources, Islamic construction.